Degradable Silk‐Based Subcutaneous Oxygen Sensors. (10th April 2022) - Falcucci, Thomas; Presley, Kayla F.; Choi, Jaewon; Fizpatrick, Vincent; Barry, Jonah; Kishore Sahoo, Jugal; Ly, Jack T.; Grusenmeyer, Tod A.; Dalton, Matthew J.; Kaplan, David L.
Abstract: Continuous monitoring of biochemical analytes like oxygen is of interest in biomedicine to provide insight into physiology and health. Silk‐protein biomaterials are particularly useful as the scaffold material in oxygen sensors due to silk's unique amphiphilic chemistry, which promotes noncovalent stabilization of the protein and additives in aqueous environments. Silk films containing a water‐insoluble oxygen‐sensing chromophore, Pd (II) tetramethacrylated benzoporphyrin (PdBMAP), are evaluated as optical oxygen sensors in vitro and in vivo. These silk‐chromophore composites are stabilized by the self‐assembled, physically crosslinked protein network. The deaerated phosphorescence lifetime (τm, 0  ≈300 µs) of the chromophore in vitro is quenched to 50% of its initial value at ≈31 µm dissolved oxygen, indicating sensing functionality within physiological ranges of oxygen. In vitro enzymatic degradation of the silk films with and without the chromophore is demonstrated. The silk‐chromophore composite films are cytocompatible in vitro, biocompatible in vivo upon implantation in rats, and displayed mechanical properties suitable for subcutaneous implantation. Further, the films maintain oxygen‐sensing function in vivo and demonstrate real‐time sensing capabilities throughout various physiological states (i.e., hyperoxia, normoxia, and hypoxia). Abstract : This study characterizes and demonstrates the functionality of an optical oxygen sensor comprised of a natural silk protein scaffold and chromophore composite. The silk‐chromophore sensing system is assessed for material integrity, degradation, and oxygen sensitivity in vitro before confirming the function of the platform in vivo when implanted subcutaneously in rats.